Evaluation of the protective effects of tocotrienol-rich fraction from palm oil on the dentate gyrus following chronic restraint stress in rats - Talip, Saiful Bhari; Asari, Mohd Asnizam; Khan, Aaijaz Ahmed; Salam Sirajudeen, Kuttulebbai Nainamohamed (Universidade de São Paulo, 2013)
Exposure to chronic restraint stress has been shown to cause a number of morphological changes in the hippocampal formation of rats. Tocotrienol, an isoform of vitamin E, exhibits numerous health benefits, different from those of tocopherol. Recent studies have demonstrated that tocotrienol prevents stressinduced changes in the gastric mucosa, thus indicating that it may also protect other organs such as the brain from the damaging effects of stress. Therefore, the aim of the present study was to investigate the protective effect of tocotrienol-rich fraction (TRF) extracted from palm oil on the dentate gyrus of rats following exposure to chronic restraint stress. Thirty-six male Sprague Dawley rats were divided into four groups: control, stress, tocotrienol and combination of stress and tocotrienol. Animals were stressed by restraining them for 5 hours every day for 21 consecutive days. TRF was administered via oral gavage at a dose of 200 mg/kg body weight. Our results showed that the plasma corticosterone level was significantly increased in response to stress, compared to the control. The results confirmed previous findings that chronic restraint stress suppresses cellular proliferation and reduces granule cell number in the dentate gyrus. However, TRF supplementation failed to prevent or minimize these stressinduced changes. Therefore, we conclude that TRF at the current dosage is not effective in preventing the morphological changes in the dentate gyrus induced by chronic restraint stress.